El lenguaje de los indigentes en la plaza de San Francisco en la Ciudad de Quito hacia una comunicación en alteridad - Gudiño Mantilla, Freddy Adrián (2015)
The language of the homeless in San Francisco Square in the city of Quito to a communication otherness. Justification: This research relates to the document MEDIACOM postulated by teacher Marco Polo Guerrero, adopted at the Salesian University. It relates to the field of Communication and Culture, whose focus raises communication, social, and cultural development; and competencies are associated to reflect, interpret and analyze communication through the elements of the local reality; and their interactions with the different manifestations of development and convergences and cultural expressions of the processes of otherness. This final work of the race will be built in the city of Quito, in the historical center from July 2014 to April 2015; for which it is referenced to the homeless who are in the Plaza de San Francisco as public space. Theoretically required to reflect on communication and interaction with men and women who live in extreme poverty. This proposal will end after a diagnosis after which, a field journal and based on a semiotic study of the language of the homeless based on a communication otherness through the interpretation and reinterpretation survey was developed. The investigation is likely to be explanatory character because he used the integral method of induction, deduction and will use survey techniques and relevant literature review and their respective instruments.